Pemeriksaan IVA Test Pada Wanita Usia Subur Di Desa Kepuharjo, Cangkringan, Sleman - Eka Vicky Yulivantina; Bima Suryantara; Ade Elvina; Evellia Lofita Dini; Nyemas Sindya Utari; Harmiawati; Maria Magdalena Theofila Duka (LPPM STIKES Guna Bangsa Yogyakarta, 2020)
Cervical cancer is the most common cancer in Indonesia that requires public health action or intervention. Screening is one way to find precancerous and cancerous lesions at an early stage. IVA examination is a screening that can be used to detect precancerous lesions for cervical cancer in all women of childbearing age who have been sexually active.